NON-BUDGETARY ASPECTS AFFECT FOOD SECURITY IN SOUTHEAST SULAWESI PROVINCE - Tajuddin, Tajuddin; Suriadi, La Ode; Anto, La Ode; Arifuddin, Arifuddin; Ariani, Wa Ode Rachmasari (Journal Economics Technology And Entrepreneur, 2025)
This study aims to examine the impact of government expenditure (APBD and APBN) on food availability in Southeast Sulawesi Province. Utilizing secondary data and elasticity analysis, the research assesses the responsiveness of food production to budgetary changes. The findings reveal that increased government spending through APBD and APBN does not significantly enhance food production. Instead, fluctuations in food output are primarily driven by non-fiscal factors, including agricultural land conversion for non-agricultural uses, declining soil productivity, climate change-induced disruptions to planting and harvesting cycles, and other external variables. Consequently, Southeast Sulawesi's food security faces long-term vulnerabilities without proactive interventions. Sustainable measures such as safeguarding and expanding agricultural land, improving farming efficiency, and adopting climate-resilient agricultural technologies are critical to mitigating these risks. Policymakers must prioritize these strategies to ensure stable and sustainable food security in the region.